Principle of Proportionality in Competition Law of the EU and Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article explores the principle of proportionality within EU law and its burgeoning relevance in Uzbekistan’s legal framework, particularly in competition law enforcement. Focusing on Uzbekistan, the article highlights recent legal reforms, such as the introduction of fining powers in 2022. Despite these reforms, challenges remain, such as the limited application of proportionality in administrative and judicial proceedings, as evidenced by the infrequent use of this principle in case law. The article underscores the importance of embedding proportionality more deeply within Uzbekistan’s legal system to ensure fair and effective competition enforcement.